2012
DOI: 10.1371/journal.pntd.0001884
|View full text |Cite
|
Sign up to set email alerts
|

Host Life History Strategy, Species Diversity, and Habitat Influence Trypanosoma cruzi Vector Infection in Changing Landscapes

Abstract: BackgroundAnthropogenic land use may influence transmission of multi-host vector-borne pathogens by changing diversity, relative abundance, and community composition of reservoir hosts. These reservoir hosts may have varying competence for vector-borne pathogens depending on species-specific characteristics, such as life history strategy. The objective of this study is to evaluate how anthropogenic land use change influences blood meal species composition and the effects of changing blood meal species composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
134
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(149 citation statements)
references
References 69 publications
13
134
1
1
Order By: Relevance
“…In contrast, females may be stationary after (Table 2), all of which were previously known to be capable of hosting the parasite [7]. 261 We did not see evidence of double peaks in our chromatographs and direct sequencing 266 always resulted in a single, uncontroversial host sequence, similar to results from other studies 267 conducted using similar primers [49], but in contrast to other studies where cloning of the PCR 268 product was performed and as many as four hosts were detected from a single specimen [50]. may reflect the sylvatic nature of most of our collecting sites and, potentially, the rigorous 278 sterilization protocol we utilized.…”
Section: Results and Discussion 237supporting
confidence: 72%
“…In contrast, females may be stationary after (Table 2), all of which were previously known to be capable of hosting the parasite [7]. 261 We did not see evidence of double peaks in our chromatographs and direct sequencing 266 always resulted in a single, uncontroversial host sequence, similar to results from other studies 267 conducted using similar primers [49], but in contrast to other studies where cloning of the PCR 268 product was performed and as many as four hosts were detected from a single specimen [50]. may reflect the sylvatic nature of most of our collecting sites and, potentially, the rigorous 278 sterilization protocol we utilized.…”
Section: Results and Discussion 237supporting
confidence: 72%
“…From previous studies in wildlife, it is clear that infection patterns can be the result of complex relationships between hosts and parasites that depend on the lifecycle and transmission mode of the parasite as well as the life history strategies, tradeoffs, and ecological context of host species (15)(16)(17). By simultaneously considering all rodent species and the zoonotic infectious agents that they are known to carry, our models identified trait profiles suggesting that rodent reservoirs are distinguished from other rodent species by a fast-paced life history strategy (Fig.…”
Section: Ecologymentioning
confidence: 99%
“…In field experiments, exposure to hantavirus increases when mammalian diversity falls (56). For Chagas disease in Panama and the Brazilian Amazon, risk of human exposure is positively correlated with reduced mammalian species diversity (57,58). This suite of findings has led to the proposal of a general principle of disease ecology-the "dilution effect"-whereby a greater diversity of intermediate hosts can dilute the pool of hosts that amplify transmission (competent hosts), resulting in decreased exposure to vector-borne disease (59,60).…”
Section: Highlights Of the Recent Literaturementioning
confidence: 99%
“…Some recent research suggests that immunological tolerance, and hence high host competence, tends to characterize the species that are intrinsically more likely to persist when diversity declines (62). Related research has indicated that hosts with a high intrinsic rate of increase are both more ecologically resilient and reservoir competent (58). Other work has emphasized the idiosyncratic nature of particular disease/ecology relationships (63), and still other efforts have concluded that generalizations about the effect of biodiversity on disease transmission have been premature (64).…”
Section: Highlights Of the Recent Literaturementioning
confidence: 99%